The right to education of asylum seeker and refugee children - Mweni, Sabelo Kenneth (Department of Public Law, 2018)
This research reviews the application of the law on the right of refugee children to education and the challenges inhibiting this right. Radical changes in the legal framework protecting refugee children's right to education has occurred since South Africa became a democratic state in 1994. The enactment of international law into the 1994 Constitution contributed into the protection of various children right and insured equal access into the education system. However, refugee children have been prejudiced in the right to access education based on numerous challenges. The lack of access education for refugee children is an unconstitutional practice in schools rather than a legislative injustice. This paper uses journal reports, newspaper articles, academic writing on both national and international perspective on the infringement of education rights on refugee children. The findings provide clarity on unconstitutional practices and the legal standpoint on such practices. The right to education constitutes a valuable foundation for integration. South Africa is obligated by both national and international law to provide immediate education to refugee children.